Detecção da atividade hemaglutinante em esponjas marinhas do litoral cearense e purificação e caracterização bioquímica de lectinas das esponjas marinhas Callyspongia vaginalis e Aplysina fulva - Torres, Renato Cézar Farias (2020)
The sponges belong to the phylum Porífera and are multicellular organisms made up of cells embedded in a gelatinous matrix and stiffened by a skeleton of spicules of calcium carbonate or silica and collagen. The interest in this phylum is inherent in the studies reported that show broad biotechnological potential of macromolecules with interesting properties, showing activity against diseases and some pathogens, and possibly capable of playing the role of a biomedical tool, such as lectins. Lectins are proteins capable of reversibly binding to specific carbohydrates, without causing structural changes in them. These proteins are able to act as recognition molecules inside cells, cell surfaces and physiological fluids. In marine sponges, lectins can perform a variety of functions, including cell interaction, spiculogenesis and defense. The aim of this work was to detect hemagglutinating activity in protein extracts from marine sponges and to purify and characterize lectins present in marine sponges Callyspongia vaginalis and Aplysina fulva. The extracts of the 11 species tested showed hemagglutinating and hemolytic activity against human and rabbit erythrocytes. Called CvP (Callyspongia vaginalis Protein), the C. vaginalis lectin was isolated from chromatographic combinations of ion exchange in DEAE-sephacel and DEAE-FF matrix. This protein is composed of three polypeptide chains linked to a chromophore with absorption at 600 nm. CvP shares high sequence similarity with H-3, lectin isolated from Haliclona caerulea. However, CvP did not show hemagglutinating activity, so it was considered a lectin-like activity. AFL (Aplysina fulva Lectin), isolated from A. fulva, was purified by precipitation with ammonium sulfate followed by affinity chromatography on Sepharose 4B matrix. The new lectin is a 30 kDa dimer, formed by two equal 15 kDa subunits linked by disulfide bridges. Its hemagglutinating activity was stable at neutral-alkaline pH and at temperatures below 60ºC. AFL activity was inhibited by pig stomach mucin glycoprotein. AFL showed potential in reducing the biofilms of the bacterial strains of Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli, being able to play an antibacterial role. Thus, two new proteins were isolated and biochemically characterized and the results presented above will serve as a basis for biotechnological application in different biological models.